Thinking Jewish culture in America - Koltun-Fromm, Ken; Koltun-Fromm, Ken (Graven images (Lanham, Md.), 2014)
Thinking Jewish Culture in America argues that Jewish thought extends our awareness and deepens the complexity of American Jewish culture. This volume stretches the disciplinary boundaries of Jewish thought so that it can productively engage expanding arenas of culture by drawing Jewish thought into the orbit of cultural studies.